Investigasi bidang gelincir di Jorong Koto Baru Nagari Aie Dingin Kabupaten Solok dengan metode geolistrik tahanan jenis konfigurasi schlumberger (Investigation of landsile slip surface in Jorong Koto Baru Nagari Aia Dingin, Solok Regency using the geoelectric resistivity method with the schlumberger configuration) - - Nurhidayati; - Akmam; Harman Amir (PILLAR OF PHYSICS, 2015)
Investigation of landslide slip surface using geoelectrical resistivity method has been conducted at Jorong Koto Baru Nagari Aie Dingin Kabupaten Solok. The aim of this research is to know the shape of slip surface, depth of slip surface, and angle of slip surface. Data were collected by Automatic Resistivity Multielectrode in 4 lines with Schlumberger configuration. Interpretation of data was done with Robust Constraint Inversion. The result of this research shows that slip surface is Translation slip. The estimation result showed that the subsurface lithology on four path consist of Alluvium and Sands, Sandstone, Clay, Limestone and Granite. The slip surface is a clay layer on four path with resistivity value range from 66.1-90.25 Ωm, 70.45–90.8 Ωm and 67.05-100 Ωm. Depth of slip surface for one and three section was found are of 7.05 meter, and for two section was found are of 4.14 meters. Angles of slip surface are 21.74°, 19.94°, 21.85°, 17.46° and 17.13°